Digital dashboards as tools for regional influenza monitoring - Sarah Hamid; Leila Bell; Erica Dueger (World Health Organization Regional Office for the Western Pacific, 2017)
The World Health Organization's Regional Office for the Western Pacific has developed an interactive online influenza platform linking data from National Influenza Centres and Influenza Surveillance in the Western Pacific Region. This platform for regional monitoring of influenza enhances the accessibility of data and information for international and national authorities.